ADAPTASI KULTURAL MASYARAKAT MULTIETNIS TEPIAN SUNGAI KAPUAS KOTA PONTIANAK DALAM KONTEKS PENDIDIKAN DAN PEMBELAJARAN - Syaifulloh, Muhammad; Wibowo, Basuki (Universitas Muria Kudus, 2024)
This study aims to determine and understand the cultural adaptation and methods of the multiethnic community on the banks of the Kapuas River in Pontianak City in the context of education and learning.This study uses a qualitative case study method. The research population includes multiethnic communities involved in formal and non-formal education. The sample was selected using a purposive sampling technique. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the Miles and Huberman interactive analysis model which includes data collection, reduction, presentation, and drawing conclusions. Data validity through triangulation of techniques and sources, with instruments in the form of semi-structured interview guides, field notes, and document checklists.The results of the study show that the multiethnic community on the banks of the Kapuas River has a rich and unique cultural diversity, with factors that influence the formation of this diversity including geographical location, history, and interaction between tribes. However, this cultural diversity is a challenge in the context of education and learning because of differences in language, ways of thinking, and values adopted by each tribe. To overcome this, an inclusive and responsive approach to cultural diversity is needed, as well as the role of teachers who understand cultural diversity and the ability to design appropriate learning. Interaction between students from various ethnicities, the use of technology in learning, and synergy between the government, educational institutions, and the community can facilitate cultural adaptation in education.